Facile Synthesis of Mayenite Electride Nanoparticles Encapsulated in Graphitic Shells Like Carbon Nano Onions: Non-noble-metal Electrocatalysts for Oxygen Reduction Reaction (ORR) - Khan, Karim; Tareen, Ayesha Khan; Aslam, Muhammad; Zhang, Yupeng; Wang, Renheng; Khan, Sayed Ali; Khan, Qudrat Ullah; Rauf, Muhammad; Zhang, Han; Ouyang, Zhengbiao; Guo, Zhongyi (Frontiers in Chemistry, 2020)
In this manuscript we present a large scale synthesis of Graphitic Shells like carbon nano onions (GS-CNOs) by direct solution method using mayenite electride as a catalyst for synthesis of CNOs. Thermal characterization, microstructural analysis, and high resolution electron microscopy have confirmed the graphitization and revealed the resulting GS-CNOs with particle size about 15 nm, maximum BET surface area of 214 m2.g-1, and moderate conductivity of 250 S.cm-1, thus providing a new approach to synthesize GS-CNOs. Here we reported, the GS-CNOs, which acts as more active but less expensive electrocatalysts with onset potential of 1.03 V, half wave potential of 0.88 V versus the reversible hydrogen electrode (RHE), and limited current density of 6.1 mA.cm-2, higher than that of benchmark 20% Pt/C (1.02eV, 0.82 V, 5.2 mA.cm-2). The synthesized nano-powder acts as an origin of ORR activity via a four electron (4e-) pathway, along with significantly enhanced stability, in alkaline media. The high ORR activity is ascribed to GS-CNOs embedded sufficient metallic C12A7:e- particles, which favor faster electron movement and better adsorption of oxygen molecules on catalyst surface. Hence, we explore first time large scale synthesis of GS-CNOs with gram level and provide efficient approach to prepare novel, lowest cost, potential non-noble metals catalyst for fuel cells.